A New Tunnel Effect? The Impact of Stress on Vote Choice - Couture, Jérôme; Breux, Sandra (Frontiers in Political Science, 2021)
While the literature does show a link between stress and voter turnout, the question remains as to what extent stress influences vote choice. Moreover, how might we explain the presence of such a relationship? Using a survey of Quebec City voters during the 2017 municipal election (n=1,130), we show that 1) there is a relationship between stress and vote choice, and 2) voters who consider road congestion to be an important issue and who declare being stressed tend to vote for the party that has taken a stand in favour of highway projects and against public transit, among other things. While many studies show that road congestion is a variable affecting the psychological health of individuals, our research invites us to consider the political impacts of such a relationship.